CAPITAL MOBILIZATION OF VIETNAM BANK FOR AGRICULTURE AND RURAL DEVELOPMENT-KHOAI CHAU BRANCH - Dao Duc Bui (Journal of Applied Science and Technology, 2019)
Particularly in banking, capital is the decisive factor for all business activities. In fact, commercial banks now own only a small percentage of capital mobilized, borrowed capital and other capital. In particular, capital mobilization always occupy the largest proportion and stability. Therefore, it can be said that the mobilization of capital plays a big role in determining the operation and development of commercial banks. Bank for Agriculture and Rural Development - Khoai Chau district branch as well as all other banks in the orientation of development, raising capital mobilization is still the top priority. Research on bank operations in recent years shows that banks always take measures to increase capital mobilization and achieve certain results, contributing to enhance prestige and competitiveness in business.